2010
DOI: 10.1016/j.resuscitation.2009.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Capnography and chest-wall impedance algorithms for ventilation detection during cardiopulmonary resuscitation

Abstract: Objective-Hyperventilation is both common and detrimental during cardiopulmonary resuscitation (CPR). Chest wall impedance algorithms have been developed to detect ventilations during CPR. However, impedance signals are challenged by noise artifact from multiple sources, including chest compressions. Capnography has been proposed as an alternate method to measure ventilations. We sought to assess and compare the adequacy of these two approaches.Methods-Continuous chest wall impedance and capnography were recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 24 publications
(30 reference statements)
3
40
0
Order By: Relevance
“…In a case series (LOE 4 110 ), capnography and chest-wall impedance algorithms were inaccurate for determining ventilation rate.…”
Section: Consensus On Sciencementioning
confidence: 98%
“…In a case series (LOE 4 110 ), capnography and chest-wall impedance algorithms were inaccurate for determining ventilation rate.…”
Section: Consensus On Sciencementioning
confidence: 98%
“…The TI signal can be used to identify CCs 17,26-28 and ventilations. 17,[29][30][31][32] Although the compression depth is associated with outcome, it has been reported that it cannot be measured using the TI signal. 33,34 Therefore, the identification of CCs and ventilations in the TI only allows to evaluate quality metrics related to presence and rate.…”
Section: Introductionmentioning
confidence: 99%
“…Algorithms for CC detection using the TI signal are integrated into commercial software for episode reviewing, and algorithms for ventilation detection have been recently proposed using the TI. 29,30 Their global performance is provided in terms of sensitivity and positive predictive value (PPV). 26 Nevertheless, detailed analysis of the utility of the TI signal for CC/ventilation metrics is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, capnography has been proposed as a method of monitoring ventilation during CPR and is especially used in basic science experiments [8]. Edelson et al suggested that the use of capnography in combination with chest wall impedance from defibrillator pads may estimate more accurately the ventilation rate [73]. As a result, hyperventilation due to increased respiratory frequency may be prevented and thus haemodynamics during CPR may improve [74].…”
Section: Other Usesmentioning
confidence: 99%